2022
DOI: 10.2147/jpr.s370469
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Guidelines on Interventional Therapies for Knee Pain (STEP Guidelines) from the American Society of Pain and Neuroscience

Abstract: Knee pain is second only to the back as the most commonly reported area of pain in the human body. With an overall prevalence of 46.2%, its impact on disability, lost productivity, and cost on healthcare cannot be overlooked. Due to the pervasiveness of knee pain in the general population, there are no shortages of treatment options available for addressing the symptoms. Ranging from physical therapy and pharmacologic agents to interventional pain procedures to surgical options, practitioners have a wide array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 395 publications
(572 reference statements)
0
17
0
Order By: Relevance
“…There are multiple case reports of Stimwave PNS for other chronic pain syndromes [18][19][20]. However, there is not enough data to advocate the use or to comment on the placement of this device in treatment algorithms in cases of refractory, chronic pain post-TKR.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple case reports of Stimwave PNS for other chronic pain syndromes [18][19][20]. However, there is not enough data to advocate the use or to comment on the placement of this device in treatment algorithms in cases of refractory, chronic pain post-TKR.…”
Section: Discussionmentioning
confidence: 99%
“…2 Regenerative treatment in the form of intra-articular PRP and mesenchymal stem cell injections have also been included in the injection-based therapy as a potential joint remodeling approach. 3 Surgical intervention, either total or partial knee replacement, is recommended for patients with severe knee OA. Bourne et al showed that one-fifth of patients were not satisfied with the outcome of total knee arthroplasty; the artificial implant has a lifespan of only 10 to 15 years, which is not suitable for young patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 A recent comprehensive consensus guideline on knee pain assigned a level 1 recommendation to safety and efficacy of intra-articular PRP for knee pain and improvement in function. 3 Studies have shown that improvement for pain and function decline starting at 6 to 9 months post-PRP injection; the optimal frequency of PRP injections remains unclear. Huang et al showed that at 12 months post-intervention, all patients had significant improvement in terms of VAC and WOMAC compared to pre-procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations